2020
DOI: 10.36446/af.2020.318
|View full text |Cite
|
Sign up to set email alerts
|

Relatividad lingüística, gramáticas de género y lenguaje inclusivo: algunas consideraciones

Abstract: En este artículo examinaremos un caso de aplicación de la hipótesis de la relatividad lingüística (HRL): la influencia del género gramatical de las lenguas sobre la cognición o el pensamiento de los hablantes. Dado que las lenguas difieren tanto en sus repertorios léxicos como sobre todo en sus gramáticas de género para referir a las personas, a otras entidades animadas e incluso a entidades inanimadas, nuestro propósito será, en primer lugar, revisar la evidencia experimental reciente que avalaría la HRL en e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
0
5
0
11
Order By: Relevance
“…Since these are instantiated differently in each language, depending on the grammatical gender paradigm (GYGAX et al, 2019), one question that arises is whether these different realizations generate different mental representations. In other words, as was suggested by Scotto and Pérez (2020), to what extent the influence of the grammatical gender of languages on cognition can be analyzed within the framework of the hypothesis of linguistic relativity. (KAUFMANN;BOHNER, 2014;LEAPER, 2014;SATO;GABRIEL, 2016;MOSER;WOOD, 2015;VIGLIOCCO et al, 2005) have shown empirical evidence of stable biases -not contingent in particular linguistic uses or specific communicative contexts-of certain linguistic forms in cognition, namely in the mental representations that we manipulate during tasks both mediated and not mediated by language.…”
Section: For Peer Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Since these are instantiated differently in each language, depending on the grammatical gender paradigm (GYGAX et al, 2019), one question that arises is whether these different realizations generate different mental representations. In other words, as was suggested by Scotto and Pérez (2020), to what extent the influence of the grammatical gender of languages on cognition can be analyzed within the framework of the hypothesis of linguistic relativity. (KAUFMANN;BOHNER, 2014;LEAPER, 2014;SATO;GABRIEL, 2016;MOSER;WOOD, 2015;VIGLIOCCO et al, 2005) have shown empirical evidence of stable biases -not contingent in particular linguistic uses or specific communicative contexts-of certain linguistic forms in cognition, namely in the mental representations that we manipulate during tasks both mediated and not mediated by language.…”
Section: For Peer Reviewmentioning
confidence: 99%
“…Extreme forms of this idea, which sustained a linguistic determinism, more than an influence or bias, have provoked opposite reactions. Some of them, also extreme (PINKER, 1999), neglect intermediate approaches or proposals, also known as weak (EVERETT, 2013;LUCY, 1996;SAPIR, 1921;SCOTTO;WHORF, 1956;ZLATEV;BLOMBERG, 2015). Initially, the hypothesis of linguistic relativity held that the language we speak shapes the way we think.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formas extremas de esta idea, que sostenían un determinismo lingüístico, más que una influencia o sesgo, han provocado reacciones opuestas también extremas (PINKER, 1999), que desatienden matices o propuestas intermedias, también denominadas "débiles" (EVERETT, 2013;LUCY, 1996;SAPIR, 1921;SCOTTO;WHORF, 1956;ZLATEV;BLOMBERG, 2015). Inicialmente, la hipótesis de relativismo lingüístico sostenía que la lengua que hablamos moldea nuestro pensamiento.…”
Section: Introductionunclassified
“…Descartar un determinismo fuerte no supone eliminar la posibilidad de analizar las múltiples y complejas formas en las que se da la relación entre pensamiento y lenguaje, o cognición, representaciones mentales y formas lingüísticas. Existen, ciertamente, diversas y muy actuales propuestas en torno a este punto (EVERETT, 2013;SCOTTO;ZLATEV;BLOMBERG, 2015): el lenguaje como "potenciador" del pensamiento, el lenguaje como "intromisión" u "obstáculo", el lenguaje como "focalizador", el lenguaje como "inductor" y algunas variantes de la conocida hipótesis de "pensar para hablar" (SLOBIN, 1991;1996). Varias de estas perspectivas han sido retomadas por estudios empíricos en el marco de la psicolingüística experimental y han logrado recolectar evidencia de respaldo para sustentar algunos modos de sesgo o influencia de las formas lingüísticas sobre la cognición.…”
Section: Introductionunclassified